(untitled) (Swiss Medical Weekly, 2022)
OBJECTIVES: We present an adolescent with cardiogenic shock due to ventricular tachycardia 2 weeks after SARS-CoV-2 infection. Acute myocarditis or myocardial dysfunction is associated with SARS-CoV-2 infection, but diagnosis may be difficult, even including endomyocardial biopsy. CASE REPORT: A 15-year-old healthy adolescent was admitted to our hospital 2 weeks after SARS-CoV-2 infection with cardiogenic shock due to ventricular tachycardia. After cardioversion, antiarrhythmic treatment, ventilation, and inotropic support, the severely reduced myocardial function recovered completely within 2 weeks. Cardiac magnetic resonance imaging and cardiac catheterisation including right ventricular endomyocardial biopsy revealed an increased number of CD68+ macrophages in the myocardium, but nested (RT-) polymerase chain reaction (PCR) investigations revealed no viral or bacterial DNA/RNA. DISCUSSION: SARS-CoV-2 infection may be associated with myocarditis leading to life-threatening arrhythmia and severe myocardial systolic and diastolic dysfunction, which may be short lasting and completely recover. Although former SARS-Cov-2 infection might suggest SARS-CoV-2-associated myocarditis, definite histological diagnosis including nested PCR investigations remains difficult.